2013
DOI: 10.1364/ol.38.003827
|View full text |Cite
|
Sign up to set email alerts
|

Active directional beaming by mechanical actuation of double-sided plasmonic surface gratings

Abstract: A novel mechanism for active directional beaming by mechanical actuation of double-sided plasmonic surface gratings is proposed. It is shown that the asymmetric mechanical actuation of optimally designed plasmonic surface gratings surrounding a subwavelength metal slit can produce a steerable off-axis beaming effect. The controllability of the beam direction provides an opportunity to develop novel active plasmonic devices and systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…(7) indicates that the diffractive waves of the left and right side grating are the same and independent with each other [21,23,24], so the characterization of the single-side grating structure as shown in Fig. 2(a) provides basic information to optimize the double-side grating structure as shown in (b).…”
Section: Results and Analysismentioning
confidence: 99%
“…(7) indicates that the diffractive waves of the left and right side grating are the same and independent with each other [21,23,24], so the characterization of the single-side grating structure as shown in Fig. 2(a) provides basic information to optimize the double-side grating structure as shown in (b).…”
Section: Results and Analysismentioning
confidence: 99%
“…By breaking the symmetry of the slit-corrugation structure, off-axis directional beaming can be achieved [15][16][17][18][19][20][21][22][23][24]. Asymmetric and/or locally non-periodic structures also enable wavefront shaping, such as focusing and splitting [25][26][27][28][29][30][31][32][33] (much in analogy with conventional diffractive optics) and the control of the beaming direction [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction problem also greatly limits integration and miniaturization of conventional optical components. Over the past few decades, advances have allowed metals to be structured and characterized on the nanometer scale, as a result, great efforts have been made to overcome the diffraction limitation with the help of surface plasmon polaritons (SPPs) on metallic surfaces [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The pioneering work of unusually high transmission through subwavelength periodic hole arrays in metal films was report by Ebbesen et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several years later, Lezec et al further reported that a metallic subwavelength slit surrounded by a periodic array of corrugation/grooves that supports the propagation of SPPs cannot only get more light through such structures but also to channel it in a well-defined direction with low divergence [8]. These discoveries have stimulated a large amount of researches in theory and experiment towards further improving beaming characteristics, especially achieving steerable off-axis beaming [9][10][11][12][13][14][15][16][17][18]. Up to now, most of the methods proposed for directional beaming are based on subwavelength metal nanoslits with dielectric surface gratings, where the periodic grating structure properties, such as the asymmetry, the period, the depth of the corrugations, and so on, need to be carefully designed for optimal beaming performance [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%